Assessment of Family Environment and Needs of Families Who Have Children with Cerebral Palsy - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2015)
Objective: The aim of the study is to identify family needs and to assess the family environment of children with cerebral palsy (CP). Material and Methods: Participants were the primary caregivers of 103 children between the age of 4 and 12 years with a diagnosis of CP. The parents of the children completed the Family Environment Scale (FES) and the modified version of Family Needs Survey (FNS). The Gross Motor Function Classification System (GMFCS) and Manual Ability Classification System (MACS) levels of children were determined. The medical history of the participants accompanying disorders and characteristics of families are questioned. Results: According to the results of FNS, the most cited requirement was need for information (84.3%) and the least cited requirements were needs for babysitting while having a meeting (62.1%) and payment for childminders (74.8%). Neither the FES nor the FNS results was correlated to the GMFCS or MACS levels or accompanying disorders. Conclusion: Regardless of education level, parents reported need for information about their children's conditions and future services. If families are informed about their children's health condition and are aware of present or future resources, better outcomes will be seen. Understanding the needs of families who have children with CP and assessment of family characteristics and environment are important for family-centered services.
Keywords: Cerebral palsy; family needs; family environment; CLASSIFICATION-SYSTEM MACS; ORAL-HEALTH; PREVALENCE; PARENTS; CARIES; YOUTH